Gender norms and women’s empowerment: The case of pig-related businesses in Uganda - Achandi, Esther Leah; Galiè, Alessandra; Ouma, Emily A.; Omondi, Immaculate A.; Farnworth, Cathy Rozel; Lukuyu, Ben A. (International Livestock Research Institute, 2023)
This study explores gender norms, women’s empowerment and the interlinkage between the two in pig-related businesses. The study adopts a qualitative methodology with single-gender focus group discussions (FGDs), key informant interviews (KIIs), and individual interviews (IIs) with respondents directly involved in or knowledgeable about norms in pig-related businesses. Findings highlight norms that shape the image of what and where a woman ought to be and the actions she can display or activities she can perform thereby affecting women’s engagement in the pig enterprise in terms of activities, places of engagement and positioning in terms of value of benefits accorded. Noncompliance to norms drew sanctions and frequent reminders about the ideal image of the woman in the society. Local conceptualization of empowerment shows the extent of the key role gender norms play in empowerment. Women understood empowerment as a process that entails a change in the traditional image of the woman as prescribed by norms in addition to frequently highlighted aspects of empowerment such as voice, independence, status and positioning. Men defined empowerment as a process along commonly held aspects of decision-making, ownership of resources but within the confines of social expectations (norms). This study implies that gender-transformative change and women’s empowerment in pig-related businesses requires engagement with both norms and empowerment gatekeepers who often play the two roles simultaneously.